L’impact des carences affectives vues par les neurosciences - Ghanem, Nafissa (Journal of Human Sciences, 2016)
In the early twentieth century, the work of Spitz psychoanalysts Bion, Anna Freud and Winnicott drew attention to the psychological problems related to emotional deprivation in identity construction. John Bowlby (1969), author of the theory of attachment, considers the trend to establish close relationships as essential to the survival of the human being. Today, with advances in MRI material, it is possible to understand how the mechanisms of the lack of attachment, in other words, emotional deprivation, and shall adjust to impact our brain. These new neurophysiological data confirm the importance of maternal care on child development, especially during the first years of life.